The Analisis Faktor yang Berhubungan dengan Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Perawat di Rumah Sakit Mega Buana Palopo Tahun 2024 - Justiani Justiani; Muh Ilyas; Sudirman Sanuddin; Zamli Zamli (An Idea Health Journal, 2025)
Hospital Occupational Safety and Health (K3RS) is a very important part of the hospital. In this study, a quantitative research design with a cross-sectional research design was used. The population in this study were all nurses at Mega Buana Palopo Hospital with a target number of 88 nurses divided into several service units. The sample used in this research was 88 respondents with sampling using total sampling. Data analysis used in this research was using IBM SPSS Statistics 29. Based on the results, the research results show that the significant value of the knowledge (X1) and K3 socialization (X2) variables is smaller than the alpha value (0.00 < 0.05) so it can be interpreted as that K3 knowledge and socialization is related to the implementation of occupational safety and health (K3) among nurses at Mega Buana Palopo Hospital. Therefore, it is hoped that hospitals can further increase the knowledge of nurses in each work unit and carry out outreach regarding information and matters relating to the management process for implementing occupational safety and health (K3). This effort can be carried out by implementing tiered training for nurses and other officers regarding K3 principles, K3 risks and how to control each existing risk or danger.